CO as a Probe Molecule to Study Surface Adsorbates during Electrochemical Oxidation of Propene. Issue 1 (14th January 2021) - Winiwarter, Anna; Boyd, Michael J.; Scott, Soren B.; Higgins, Drew C.; Seger, Brian; Chorkendorff, Ib; Jaramillo, Thomas F.
Abstract: A major challenge in the electrochemical oxidation of hydrocarbons is understanding the formation of intermediate species, some of which continue to react, while others are non‐reactive or poisonous species that block adsorption of further reactants. Herein we investigate the identity and behavior of adsorbates formed during partial oxidation of propene. We employ two techniques: Electrochemistry‐Mass Spectrometry (EC‐MS) and Attenuated Total Reflection Infrared Spectroscopy (ATR‐FTIR). In both cases, we use CO as a probe molecule, to perturb the ad‐layer of propene intermediates. In the EC‐MS experiments, propene and its intermediates were quantified by triggering their desorption via displacement with CO. We show evidence for at least two distinct classes of propene adsorbates, via CO displacement and electrochemical stripping. A redshift in the ν(C−O) mode was observed, during IR spectroscopy, reflecting the chemical environment arising from strongly bound propene intermediates. Abstract : The formation of intermediate species is a major challenge in understanding the electrochemical oxidation of hydrocarbons. The authors investigate adsorbate species taking part in the partial oxidation of propene by Electrochemistry‐Mass Spectrometry (EC‐MS) and Attenuated Total Reflection Infrared Spectroscopy (ATR‐FTIR) using CO as a probe molecule. They show evidence for at least two distinct classes of propene adsorbates.